POTENTIAL FOR EFFECTIVE DEVELOPMENT OF SMALL BUSINESS IN NAMANGAN REGION - Ganiev Botir Bakhtiyorovich, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2024)
Entrepreneurship is a dynamic, active element of business, defined as an active, independent activity carried out by citizens and their associations to produce products, perform work and provide services at their own risk and property responsibility, with the goal of obtaining profit. Only the entrepreneur participates in running a business, not all market participants. Business, as mentioned above, is a broader concept than entrepreneurship. Because it covers all the relations that arise between all participants of the market economy, including not only entrepreneurs, but also consumers, employees, and state structures. Therefore, entrepreneurship is a category of business as an economic phenomenon.